Bioactive Properties of Commercially Cultivated Spirulina platensis in Indonesia: Evaluation of Anticancer and Antioxidant Potentials - Tarman, Kustiariyah; Safithri, Mega; Saputra, Rahadita Maura Amanda; Silitonga, Ria Gusharani; Dwicesaria, Maheswari Alfira; Wong, Chen Wai; Setyaningsih, Iriani (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
Spirulina platensis is a commercially cultivated cyanobacterium known for its rich bioactive compounds, including phenolics, flavonoids, and phycocyanin, which contribute to its antioxidant and anticancer properties. While previous studies focused on laboratory-grown strains, this study evaluates the total flavonoid and phenolic content, antioxidant activity, and in vitro anticancer effects of ethanol extracts from two commercial manufacturers (MA and MB). The antioxidant potential was assessed using DPPH and FRAP assays, while cytotoxicity against A549 lung and HeLa cervical cancer cells was determined via MTT assays. Results indicated that MB exhibited higher flavonoid (12.52 ± 0.23 mg QE.g-1 DW) and phenolic content (19.10 ± 0.66 mg GAE.g-1 DW) than MA, correlating with stronger antioxidant activity (FRAP: 16.55 ± 0.1 µmol TE.g-1 DW vs. 11.1 ± 0.29 µmol TE.g-1 DW). DPPH inhibition reached 80.33% (MA) and 77.77% (MB). MB also demonstrated greater anticancer activity, with 28.31% inhibition in A549 cells at 100 ppm, compared to MA’s 20.6%, and 33.85% inhibition in HeLa cells at 50 ppm. Both extracts displayed preferential toxicity toward cancer cells over normal Chang cells, supporting their potential as safer alternatives to chemotherapy. This study confirms the dual therapeutic potential of commercially cultivated S. platensis as an antioxidant and anticancer agent, highlighting its applications in pharmaceutical and nutraceutical industries. Further research is recommended to isolate and identify the bioactive compounds responsible for its cytotoxic effects.